Metabolic and cardiorespiratory responses in young oarsmen during prolonged exercise tests on a rowing ergometer at power outputs corresponding to two concepts of anaerobic threshold - Bourgois, J.; Vrijens, J. (European Journal of Applied Physiology, 1998)
A group of ten young experienced oarsmen [mean age 17.5 (SD 1.7) years, height 182.5 (SD 5.9) cm, body mass 77.0 (SEM 10.6) kg] exercised in a progressive incremental test (PIE: 50W x 3 min[-1]) on a rowing ergometer to determine the power output corresponding to the 4 mmol lactate x l(-1) anaerobic threshold (AT4) and the individual anaerobic threshold (IAT). Within 10 days they performed at random two 30-min prolonged exercise tests (PET) at power outputs corresponding to AT4 and IAT to demonstrate whether or not a steady-state blood lactate concentration [La-]b could be maintained. Oxygen uptake (VO2), heart rate (HR) and [La-]b were measured. The PIE revealed significant lower values at IAT compared to AT4 for power output (P < 0.01), HR (P < 0.01) and VO2 (P < 0.01). Coefficients of correlation between AT4 and IAT were 0.68 for power output, 0.79 for HR and 0.70 for VO2. All the subjects could complete the PET at IAT and only six out of the ten at AT4. The [La-]b at the end of PET was significantly higher at AT4 compared to IAT (P < 0.01). Similar results were found for VO2 (P < 0.01) and for HR (P < 0.01). A steady state of mean blood lactate concentration ([La-]ss was found only for the power output at IAT. From the results of this study, we concluded that both concepts of anaerobic threshold gave different information about submaximal endurance capacity. Only IAT represented on average [La-]ss. It is suggested that more research is needed to elicit optimal guidelines for the intensity of endurance training.